Global Assessment of Pediatric Patient Safety Tool for identifying safety incidents in pediatric patients - Marilise Borges Brandão; Ana Paula Hermann; Mônica Nunes Lima (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: The aim of this study was to evaluate the accuracy of the Global Assessment of Pediatric Patient Safety (GAPPS) in order to identify patient safety incidents with patient harm or adverse events (AEs). Methods: This is a cross-sectional, retrospective study of 240 records of hospitalized patients of both genders under 18 years of age, systematically and randomly selecting 10 charts of patients that meet the GAPPS criteria every 15 days from the 4,041 records of 2017. Results: The prevalence of AEs was 12.5%, i.e., detected in 30 out of 240 medical records. In total, 53 AEs and 63 harm were recorded, of which 53 (84.1%) were temporary and 43 AE (68.2%) were definitely or probably preventable. The presence of at least one trigger in a medical chart revealed 13 times greater chance of the occurrence of an AE, with sensitivity index of 48.5%, specificity of 100%, and accuracy of 86.5%. Conclusion: GAPPS was effective in detecting patient safety incidents with harm or AE.